2022
DOI: 10.1002/ctm2.816
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and transcriptomic features of persistent exacerbation‐prone severe asthma in U‐BIOPRED cohort

Abstract: Background Exacerbation‐prone asthma is a feature of severe disease. However, the basis for its persistency remains unclear. Objectives To determine the clinical and transcriptomic features of frequent exacerbators (FEs) and persistent FEs (PFEs) in the U‐BIOPRED cohort. Methods We compared features of FE (≥2 exacerbations in past year) to infrequent exacerbators (IE, <2 exacerbations) and of PFE with repeat ≥2 exacerbations during the follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…In conclusion, the study by Hoda and colleagues 7 has provided new data on transcriptional factors in blood and airway samples associated with frequent exacerbations in severe asthma. Interestingly, increased CEACAM5 expression in bronchial biopsies was associated with frequent exacerbator status, whereas transcripts in other compartments did not differ between exacerbator subgroups.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…In conclusion, the study by Hoda and colleagues 7 has provided new data on transcriptional factors in blood and airway samples associated with frequent exacerbations in severe asthma. Interestingly, increased CEACAM5 expression in bronchial biopsies was associated with frequent exacerbator status, whereas transcripts in other compartments did not differ between exacerbator subgroups.…”
mentioning
confidence: 90%
“…In the U‐BIOPRED study, former smoking was associated with increased exacerbations at baseline, 7 whereas in the UK Severe Asthma Registry population, a past smoking history correlated with frequent exacerbations only in patients on maintenance oral corticosteroids 3 . Unexpectedly, Hoda and colleagues 7 found that current smoking status was associated with a reduced risk of persistent frequent exacerbations, whereas other studies have reported that current smoking status 8 or high pack‐year history 1 was associated with an increased risk of exacerbations in severe asthma. The reason for the contrasting findings is uncertain but may be due to differences between study populations in the proportion of current and former smokers, cumulative smoking history, oral corticosteroid use, or other variables.…”
mentioning
confidence: 99%
See 3 more Smart Citations